ナンキョク サン コウソウ PHYLLOPHORA ANTARCTICA A ET E S GEPP ノ コウゴウセイ カッセイ ニツイテ ヨホウ - 大野, 正夫; オオノ, マサオ; OHNO, Masao (国立極地研究所, 1976)
P(論文) 東オングル島,昭和基地沿岸で採集された南極産紅藻Phyllophora antarctica A.et E.S.GEPPを用いて,「ふじ」船内でウィンクラー法によって光合成活性と照度・温度との関係を検討した.光合成量は純光合成量(みかけ光合成量)で求めた.光合成活性-照度曲線は,8,000lxまで照度が増すにつれ高い値を示した.光合成活性-温度曲線は,20℃付近で最高値を示した.しかし15℃と20℃の温度条件では,3日の間に葉体の脱色が進み,光合成活性も著しく低下することがわかった. Antarctic red alga, Phyllophora antarctica A. et E. S. GEPP was collected from beneath the ice on the coast of East Ongul Island (Lat. 69°00'S, Long. 39°35'E) situated in Lutzow-Holm Bay, Antarctica. The water temperature was -0.5℃. The light intensity was 650lx. The measurement of photosynthetic activity on the specimens was made in the laboratory aboard the ice breaker FUJI. The fronds were placed in D. O. bottles for one hour. Net photosynthesis was measured by means of Winkler titration for dissolved O_2 before and after the incubation. The photosynthetic activity increased with increase in light intensity till 8,000lx. The optimum temperature for the photosynthetic activity was about 20℃ under 8,000lx. But the fronds kept under 15℃ or 20℃ for 3 days discolored and showed low rates of the activity. departmental bulletin paper